A randomized crossover study comparing trehalose/hyaluronate eyedrops and standard treatment: patient satisfaction in the treatment of dry eye syndrome - Pinto-Bonilla JC; del Olmo-Jimeno A; Llovet-Osuna F; Hernández-Galilea E (Dove Medical Press, 2015)
Juan Carlos Pinto-Bonilla,1 Alberto del Olmo-Jimeno,2 Fernando Llovet-Osuna,3 Emiliano Hernández-Galilea4 1Department of Corneal, Refractive, and Cataract Surgery, European Ophthalmological Institute, Clínica Baviera, Pamplona, Navarra, Spain; 2Optometry Department, European Ophthalmological Institute, Clínica Baviera, Pamplona, Navarra, Spain; 3Department of Refractive and Cataract Surgery, European Ophthalmological Institute, Clínica Baviera, Madrid, Madrid, Spain; 4Ophthalmology Department, Hospital Clínico Universitario de Salamanca, Universidad de Salamanca, Salamanca, Salamanca, Spain Abstract: Dry eye is a common disorder in routine ophthalmological practice, and a better understanding of the complex pathophysiology is leading to improved treatment. Thealoz Duo® is a novel artificial tear preparation containing two active ingredients: Trehalose, a naturally occurring disaccharide with anhydrobiotic functions in many organisms, and hyaluronate, a widely distributed anionic glycosaminoglycan polysaccharide with lubricative and water-retaining properties in biological systems. In a randomized, single center, open label, crossover study, 17 adult patients with moderate-to-severe dry eye syndrome were randomized to treatment with Thealoz Duo® (combining trehalose and hyaluronic acid) or Systane®. Patients received 7 days of treatment. The primary efficacy variable was patient satisfaction evaluated by a 0–100 visual analog scale evaluated on days 0 and 7 of treatment. Secondary parameters included ocular surface disease index (OSDI), symptoms of dry eye, ocular staining scores (fluorescein and lissamine green), ocular clinical signs, Schirmer test, tear breakup time, and global efficacy assessed by the patient and the investigator. Seventeen patients were included. Patient satisfaction improved from 44.5±19.0 to 70.2±19.2 mm during Thealoz Duo® treatment and from 47.2±23 to 57.1±19.1 mm during Systane® treatment (P=0.043, mixed-effects analysis of covariance). Two secondary efficacy parameters (dry eye symptoms and the impact of their symptoms on work) showed statistically significant advantages for Thealoz Duo® over Systane®. There were no statistically significant advantages for Systane® over Thealoz Duo® for any measured parameter. No adverse events were reported. Thealoz Duo® appears to be an effective combination of two active ingredients for the treatment of dry eye and is at least as effective as Systane®. Keywords: dry eye, Thealoz Duo®, Systane®, patients, eyedrop, tears